(untitled) (Research, Society and Development, 2022)
Purpose: The objective of this study was to evaluate the effects of Gamma irradiation by simulating a total dose of conventional head and neck cancer radiotherapy on bone remodeling and osseointegration of implants in femurs of rats.Materials and Methods: Sixty rats received threaded titanium (Ti6Al4V) implants in both femurs. The animals were divided: No-Irradiation (N-Ir): N-Ir group with implant solely, Early-Irradiation (E-Ir): implant + irradiation after 24hrs.; Late-Irradiation (L-Ir): implant + irradiation after 4 weeks and Previous-Irradiation (P-Ir): irradiation + implant after 4 weeks. Irradiation was fractioned in two sessions of 15 Gy each, totaling 30 Gy. The animals were euthanized at 3 days, 2 and 7 weeks after treatment, which were chosen from previous studies. Runx2 immunohistochemical markers and Picrosirius red stain, histomorphometric analysis (BIC and BAFO) and reverse torque test were used to evaluate the implant/bone interface and surrounding bone. Data of Runx-2 (%), picrosirius red stain (%), BIC and BAFO (%), and reverse torque (N/cm) was submitted to ANOVA and Tukey tests for comparison among groups, both with α=0.05. Results: The results showed that Runx-2 expression was different in irradiated groups when compared to N-Ir group. In general, the collagen fiber analyses in the irradiated groups differed from the N-Ir group. Regarding BIC, BAFO, and the reverse torque test, the L-Ir group demonstrated results similar to the N-Ir group, while the others groups were impaired by radiotherapy. Conclusions: Ionizing radiation negatively affected bone remodeling, and its effect depends on when radiotherapy is applied, with a delay of osseointegration when applied previously or close to surgery.